Enhanced Leaching of Lepidolite by Acidophilic Microorganisms Under Mechanical Activation - Jingna Li; Mengyuan Wang; Ruiyong Zhang; Hongchang Liu; Shiyun Huang; Yang Liu; Rui Liao; Arevik Vardanyan; Jinlan Xia; Jun Wang (Microorganisms)
In recent years, mechanical activation technology has been extensively applied as a pretreatment process to increase the leaching efficiency in hydrometallurgical mineral processing. However, studies on its application in the lepidolite bioleaching process are limited. Therefore, the effects of mechanical activation on lithium extraction by an acidophilic iron/sulfur-oxidizing microbial community under different nutrient conditions were evaluated in this study. The solution behavior, phase morphology, and compositional evolution, and microbial community structure succession under eutrophic conditions with exogenous pyrite as the energy substrate and oligotrophic conditions, were investigated. The results revealed that mechanical activation significantly influences the microbial community structure and the interrelationship between microbial activity and mineral phase decomposition and transformation by altering the physical and chemical properties of lepidolite. The best leaching effect was observed in the eutrophic bioleaching groups, followed by the oligotrophic groups at all mechanical activation times. Notably, at a rotation speed of 200 r/min, a material-to-ball mass ratio of 1:20, and an activation time of 150 min, the maximum leaching rates of lithium under eutrophic and oligotrophic conditions were 24.9% and 20.8%, respectively, which were 20.0% and 17.9% higher than those of the nonactivated group. The phase and composition analyses indicated that the dissolution of lithium silicate minerals occurs through a combination of protic acid corrosion, the complexation/electrostatic interactions of extracellular polymeric substances, and the complexation of secondary minerals. These results indicate that the leaching effect is closely related to the pretreatment of mechanical activation, the energy substrates, and the microbial community structure, and this has important reference value for the optimization of the bioleaching process of lepidolite.